Sport-Orthopädie - Kraus K; Doyscher R; 3; Schütz E (Deutsche Zeitschrift für Sportmedizin, 2015)
Aim: The FMS is widely used to assess motor control and to estimate injury risk. However, the proceeding injury-risk-validation has shown contrary evidences. Unlikepromising pilot-studies, current studies identified a low diagnostic accuracy of the FMS cut-off score. A potential explanation for this might be the inhomogeneous factor structure which raises questions about the sum score application. Methods: 445 professional and lay sportsmen were analyzed in order to determine the item difficulty and the item discrimination of the FMS tasks. The item difficulty index described by Lienert and Raatz as well as item discrimination index by Ary were used to evaluate item difficulty and item usefulness of the FMS screening battery.Results: The item analysis describes the FMS as a difficult screening battery (Index 37.7). Generally, the items range from easy to very difficult. Within the group of Olympic athletes (n=290), item difficulty of the screening battery is described as moderate (Index 45). Rotary Stability represents the most difficult item in both groups. In contrast to more complex movement tasks, simple tasks are highly associated with the FMS sum score.Discussion: The practical value of our examination is the possible classification of the FMS into two categories. Category one is screening for local musculoskeletal flexibility which is to a certain extend a necessary prerequisite for category two - the evaluation of basic motor performance. In order to estimate injury-risk, the gathered information by the FMS seems to be not specific enough to make serious injury-risk-prognosis.KEY WORDS: FMS Sum Score, Injury Risk, Injury Prevention, Pre-Participation Screening, Item Analysis